PENGENDALIAN USAHA PERTAMBANGAN DI KABUPATEN BANDUNG BARAT - Pratiwi Pratiwi; Rita Myrna; Sawitri Budi Utami (Universitas Padjadjaran, 2021)
ABSTRACTThe extraction of mining minerals causes environmental damage carried out in protected areas, and the number of permits for these areas is increasing every year. In addition, there are still many illegal mines that are still operating. The purpose of this research is to find out and analyze how to control how the mining business control in West Bandung Regency is implemented. The author conducts an analysis using the control theory of Gareth R. Jones and Jennifer M. George, who suggest that there are four control measures, namely Establish the standards of performance, goals, or targets against which performance is to be evaluated, Measure actual performance, Compare actual performance against chosen standards of performance, Evaluate the result and initiate corrective action if the standards are not being achieved. The research method used is a research method with a qualitative approach, and data collection techniques are carried out using observation, interviews and documents. And to validate the author's data using source triangulation techniques. The results of this study indicate that the control of the mining business in the West Bandung Regency has not run effectively and efficiently. This can be seen from field inspections that have not been carried out on all mining companies; there are still violations contrary to existing standards. Then in taking action, if there are violations, there is no firm action such as giving fines to determining business actors. ABSTRAKTerjadinya kerusakan lingkungan yang disebabkan oleh pengambilan bahan galian tambang yang dilakukan di Kawasan lindung dan jumlah izin untuk Kawasan tersebut semakin bertambah setiap tahunnya. Selain itu masih banyaknya tambang ilegal yang masih saja beroperasi. Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisa bagaimana pengendalian bagaimana pengendalian usaha pertambangan di Kabupaten Bandung barat dilaksanakan. Penulis melakukan analisis menggunakan teori pengendalian dari Gareth R. Jones dan Jennifer M. George, yang mengemukakan terdapat empat langkah pengendalian yaitu Establish the standars of performance, goals, or targets against which performance is to be evaluated, Measure actual performance, Compare actual performance against chosen standards of performance, Evaluate the result and initiate corrective action if the standars is not being achieved. Metode penelitian yang digunakan adalah metode penelitian dengan pendekatan kualitatif dan Teknik pengumpulan data dilakukan dengan cara observasi, wawancara dan dokumen. Dan untuk memvalidasi data penulis menggunakan teknik triangulasi sumber. Hasil penelitian ini menunjukan bahwa pengendalian usaha pertambangan di Kabupaten Bandung Barat belum berjalan dengan efektif dan efisien. . Hal tersebut dilihat dari pemeriksaan lapangan yang belum dilakukan terhadap seluruh perusahaan tambang, masih terdapat pelanggaran-pelanggaran yang bertentangan dengan standar yang ada, Kemudian dalam melakukan penindakan apabila terdapat pelanggaran Belum adanya tindakan secara tegas seperti pemberian denda untuk memberikan efek jera kepada para pelaku usaha pertambangan.